Peran Kepemimpinan Digital Dalam Meningkatkan Kinerja Organisasi Pendidikan: Literature Review - Syarqowi, Muhammad; Zuhaery, Muhammad; Hidayati, Dian (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2025)
This study aims to analyze the role of digital leadership in improving the performance of educational organizations through a systematic literature review. The research method used a literature review approach with a focus on articles related to digital leadership and improving the performance of educational organizations. The literature search was conducted through the Scopus database using the Publish or Perish application with the keywords "organizational performance, digital leadership, and education" in the 2015-2024 publication range. Of the 22 articles found, 4 articles that met the inclusion criteria were selected for in-depth analysis. The results showed that digital leadership has a positive impact in facing operational challenges due to digitalization, encouraging innovation, and improving human resource management. Important aspects of digital leadership include visionary leadership, digital citizenship, digital-age learning culture, systemic improvement, and excellence in professional practice. However, several challenges were identified such as difficulties in nonverbal communication, limitations in digital feedback, and gaps in the application of emotional intelligence and knowledge sharing. To optimize digital leadership, the study recommends strengthening non-verbal communication through video media, employee self-leadership development, role change training, and building support mechanisms. In conclusion, digital leadership requires a comprehensive and structured approach to create an innovative and productive organizational environment in the digital age.